PAMFLET NA SZWEDZKĄ KRÓLEWNĘ JAKO ŹRÓDŁO WIEDZY O „SZPETNEJ CZAROWNICY”, CZYLI O ANNIE WAZÓWNIE - Ojcewicz, Grzegorz (Acta Neophilologica, 2013)
The author analyzes a piece of 17th century chronicle of Charles IX of Sweden and its Polish translation done by Julian Ursyn Niemcewicz. This fragment presented in a satire form concerns critics of behavior and private life of Anna Vasa (1568–1625), a niece of the king of Sweden. Both Old Swedish and Old Polish texts are valuable sources of information about the Swedish princess as the information about her private life is very scarce. The analyzed satire presents real and dubious facts (where the credibility is concerned) of the princess’s biography.